The Power of Religious Leaders to Foster Organizational Commitment in Islamic Boarding School - Nawawi, Nawawi (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to empirically identify, map, and analyze the specific sources of Kiai Power encompassing both Position Power and Personal Power that foster organizational commitment within the Islamic Boarding School environment, thereby addressing a research gap concerning the precise mechanisms of Kiai Power. Employing a qualitative approach with a multi-case study design focusing on Kiai Abdullah Syam (PRAA) and KH Soleh Bahruddin (PN), the research collected data through in-depth interviews, participatory observation, and documents. The key findings reveal that the Kiai's power to drive organizational commitment stems from five unique dimensions: Charismatic, Spiritual, Moral, Social, and Instrumental Power. Compared with Kiai Syam, Kiai Bahruddin's power is dominated by Boundary-Spanning Power through grassroots social capital and real community intervention, whereas Spiritual Depth and Institutional Power dominate Kiai Syam’s power via Tarekat sanad and formal assets. Consequently, these forces collectively generate commitment through two mechanisms: affective loyalty or moral commitment (driven by charismatic, spiritual, moral power) and calculative commitment (driven by social and instrumental power). The contribution of this study is to provide a profound understanding of the multidimensional religious leadership typology, to offer an evidence-based framework for leadership influence mechanisms in Islamic Boarding Schools, and to present practical recommendations for maintaining organizational cohesion amid demands for managerial professionalization.